Manejo ortodóncico de caninos maxilares retenidos (2002)
ABSTRACT: The orthodontic management of canine retention is based in an adecuate diagnosis, treatment and biomechanics. There is an ideal orthodontic biomechanics when there is control in the action and reaction zone. Various techniques are used: edgewise, segmentary technique, box loops, ballista spring and magnets. Most importantly, an accurate diagnosis leads to a priority list that guides to an adecuate interdisciplinary management.